Ann Cathrin November Høibo: I don’t need you anymore, I’m into Carl Andre now - Veiteberg, Jorunn (Cappelen Damm Forskning, 2026)
This book is about one work: the sculpture I don’t need you anymore, I’m into Carl Andre now (2010/2017) by Ann Cathrin November Høibo. Since completing her studies in 2010, Høibo has become a key figure in contemporary art in Norway. Textiles, in the form of found garments and hand-woven tapestries, are central to her work. With a starting point in a feminist perspective, this book explores the position of textiles as both a material and a tradition in visual art today, as well as how Høibo’s art often evades categorization: In the work in question, the textiles are combined with plastic, metal and a framed collage, such that the result is more a sculpture than a work of textile art. Material and materiality have long been neglected topics in art history, but here, the method is to follow the materials. By examining the various materials from which the sculpture is composed, layers of meaning are revealed. Through the choice of materials, a dialogue arises with Navajo blankets and with artists such as Hannah Ryggen, Else Marie Jakobsen, Carl Andre and Joseph Beuys. In the organization of the materials, the artist references art movements such as minimalism and conceptual art. By delving into this one work, the author shows how a conceptual approach can be effectively combined with a strong sense of materials. On a more general level, the book is also an investigation of how one can write about contemporary artworks that defy established categories.